Dynamics of differential count in dengue - A. Joshi, Anagha; B. R., Gayathri; Muneer, Fazeela (International Journal of Advances in Medicine, 2018)
Background: Dengue can occur as epidemics in India. Early diagnosis reduces mortality. Differential white cell count can aid in diagnosing and prognosticating Dengue in resource limited areas. Aim and objectives of this study were to assess patterns and utility of Differential counts in Dengue. Methods: A total of 132 serologically positive Dengue cases were analysed over the month of November 2016. Hematology data obtained from analysers and Leishman smears were tabulated and analysed. Results: The study showed lymphocytosis as the predominant pattern (65%) followed by neutropenia (30%), neutrophilia (11%), eosinophilia (5%), monocytosis (5%) and basophilia (4%). Atypical lymphocytosis ≥ 15% were noted in 65% of the cases with 83% showing Plasmacytoid lymphocytes, 8% apoptotic lymphocytes and 43% showed other atypical lymphocytes. Also, 52% of lymphocytosis and 33% of neutrophilia cases showed severe thrombocytopenia (≤ 0.5 lakhs per cu mm). Lymphocytosis was noted to be an early event but was established in later stages as seen with serology pattern association, 28% associated with NS1 antigen test (non-structural protein 1) and 42% with antibody pattern. However, neutrophilia with 60% of cases seen in antibody pattern was a late event. Plasmacytoid lymphocytosis was noted uniformly through all serology patterns in contrast with other atypical lymphocytosis which was seen mostly (48%) in antibody pattern. Apoptotic lymphocytosis was also a late event associated mainly with antibody pattern (55%). Conclusions: The Differential white cell count can be a useful supplementary test along with serology in resource limited peripheral areas. It additionally serves to drastically reduce morbidity and mortality.